The Influence of ESG on the Firm Value of the Mining Subsector Listed on the IDX - Supandi Dedi; Nurhaliza Nurhaliza; Fiarani Mesil; Quro Umul (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2026)
This study analyzes the effect of Environmental, Social, and Governance (ESG) disclosure on firm value in mining subsector companies listed on the Indonesia Stock Exchange (IDX), with Return on Assets (ROA) and Debt-to-Equity Ratio (DER) as control variables. The study uses a causal associative quantitative approach with secondary data from annual reports, sustainability reports, and capital market data for the period 2022–2025. The results show that ESG disclosure has no significant and negative effect on firm value, while ROA and DER have a positive and significant effect. These findings indicate that ESG disclosure has not yet become a major factor in market valuations, and investors in the mining subsector in Indonesia are still more focused on financial performance than sustainability disclosures in assessing firm value and have a negative effect because investor responses can burden companies.